2016
DOI: 10.1007/s00041-016-9468-8
|View full text |Cite
|
Sign up to set email alerts
|

Convergence Properties of Spline-Like Cardinal Interpolation Operators Acting on $$\ell ^p$$ ℓ p Data

Abstract: In this article, we provide examples of interpolation and approximation methods for p data. We also show that the resulting interpolants share convergence properties similar to those enjoyed by splines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Radial basis cardinal interpolation also enjoys a strong connection with classical sampling theory, as evidenced by much of the aforementioned literature. This connection continues to be explored in recent developments by the second author [23,24], and by parts of this article. As this is one of the most interesting aspects of cardinal interpolation, we provide some of the motivation.…”
Section: Introductionmentioning
confidence: 70%
“…Radial basis cardinal interpolation also enjoys a strong connection with classical sampling theory, as evidenced by much of the aforementioned literature. This connection continues to be explored in recent developments by the second author [23,24], and by parts of this article. As this is one of the most interesting aspects of cardinal interpolation, we provide some of the motivation.…”
Section: Introductionmentioning
confidence: 70%
“…In particular, we assume from here on that φ > 0 on R d . Cardinal functions associated with radial basis functions have been studied rather extensively [4,5,10,11,22,23,25,33,34,[36][37][38][39]41]. Specifically, the cardinal functions associated with the Gaussian and general multiquadrics are known to have nice decay (exponential in the former case and polynomial based on the exponent α in the latter).…”
Section: Examplesmentioning
confidence: 99%
“…. , c 7 ) 100 (10,16,16,9,28,20, 2) 200 (21,31,31,17,56,39,5) 300 (31,47,47,26,83,59,7) 400 (42,62,62,34,111, 79, 10) 500 (52,78,78,43,139,98,12) Table 1. Cost distribution for f with sparse wavelet representation.…”
Section: Proof Of Theorem 92 First Note That Imentioning
confidence: 99%
“…Some of this connection has been detailed in [2], where similar L 2 convergence properties are exhibited for the associated fundamental functions of interpolation. A result concerning general L p , 1 < p < ∞ results may be found in [3]. In [4], it was shown that polyharmonic splines may be used to generate multiresolution analyses.…”
Section: Introductionmentioning
confidence: 99%